Enzyme function is regulated by its localization. (December 2015) - Gifford, Stacey M.; Meyer, Pablo
Graphical abstract: Highlights: MurG membrane localization is determined by an amphipathic helix. Cardiolipin also plays a role in MurG localization to the membrane. Membrane localization correlates with MurG function in cells during sporulation. Abstract: To better understand how enzyme localization affects enzyme activity we studied the cellular localization of the glycosyltransferase MurG, an enzyme necessary for cell wall synthesis at the spore during sporulation in the bacterium Bacillus subtilis . During sporulation MurG was gradually enriched to the membrane at the forespore and point mutations in a MurG helical domain disrupting its localization to the membrane caused severe sporulation defects, but did not affect localization nor caused detectable defects during exponential growth. We found that this localization is dependent on the phospholipid cardiolipin, as in strains where the cardiolipin-synthesizing genes were deleted, MurG levels were diminished at the forespore. Furthermore, in this cardiolipin-less strain, MurG localization during sporulation was rescued by external addition of purified cardiolipin. These results support localization as a critical factor in the regulation of proper enzyme function and catalysis.